Pemikiran Al-Syatibi Tentang Maslahah Mursalah Dan Implementasinya Dalam Pengembangan Ekonomi Syariah - Khodijah Ishak (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2014)
Scholarly agreed that Syari' does not establish laws, except for realizing the human benefit. Benefit or islah the main source and the fundamental principles of legal determination. Application of the method in the determination of an issue of Islamic law in this author examines thought of Al-Syatibi, which defines maslahah mursalah is found in the new cases that are not designated by the particular texts, but it contains the benefit of the line (al-munasib) by the action of Personality. In line with the action ahsyaruffah Personality. In this case, does not have to be supported by specific arguments of stand-alone and pointed at maslahah but it can be a collection of arguments provide a definite benefit (qat'i). New problems that there is no confirmation, either justified or rejected and it contains the benefit of which is decided by maslahah mursalah is related to problems Muamalat, not related to worship. Mursalah maslahah uses as the proposition of law only to the needs of nature dharûrî and Hajj. Determine the benefit of an action that will be used as a basis for consideration in maslahah mursalah can use the argument of the maximum sense.